An asphalt network crack repairing material, a preparation method and a construction method thereof
Patent Information
- Application Number
- CN202611321720.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-28
- Publication Date
- 2026-10-30
AI Technical Summary
传统铣刨重铺工艺需对病害区域进行大面积铣刨、重新摊铺热拌沥青混合料,施工需依赖大型摊铺机、压路机等专业设备,人力物力投入大,单平方米修复成本高,施工周期长,需长时间封闭交通,对交通通行影响极大,不适用于城市主干道、交通干线等不允许长期断交的场景
本发明通过磷酸镁水泥与硫铝酸盐水泥的复合改性,赋予修复材料优异的快硬早强特性,加快了初凝时间和终凝时间,大幅缩短了施工和养护所需时间。修复材料添加有乳化沥青,呈稳定的可流动状态,可有效渗入网裂细微缝隙内部,固化后可与原沥青路面形成连续、稳定的整体化结构,实现了对网裂病害的根治,而非仅有表面封闭;同时材料与原沥青路面的相容性好,弹性模量匹配度高,界面粘结强度高,避免了界面开裂、脱落等问题,有效提升了路面结构的完整性,大幅延长了沥青路面的使用寿命。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of road engineering asphalt pavement maintenance and repair technology, and particularly relates to an asphalt network crack repair material and its preparation and construction methods. Background Technology
[0002] The information disclosed in this background section is intended only to enhance understanding of the overall background of the invention and is not necessarily to be construed as an admission or in any way implying that such information constitutes prior art known to those skilled in the art.
[0003] Under the combined effects of long-term heavy traffic loads, temperature and humidity cycles, rainwater erosion, and ultraviolet aging, asphalt pavements are prone to early-stage defects such as cracking, network cracking, and asphalt surface peeling.
[0004] Network cracking is characterized by dense, fine cracks. If not repaired promptly and effectively, rainwater will continuously seep into the pavement structure and subgrade along these cracks, leading to a rapid decline in pavement load-bearing capacity and subsequently causing serious damage such as potholes, subsidence, and pumping. This not only significantly shortens the service life of asphalt pavements but also substantially increases subsequent maintenance costs. Furthermore, road repairs require prolonged traffic closures, placing immense pressure on trunk highways and urban roads. In addition, existing repair materials generally suffer from poor resistance to shrinkage cracking, low interfacial bond strength, and weak resistance to water damage. After curing, they are prone to self-shrinkage cracking, delamination from the original asphalt pavement, and secondary rainwater infiltration, resulting in poor repair durability and the need for repeated repairs, further exacerbating the burden of road maintenance and traffic congestion.
[0005] Existing repair technologies for asphalt pavement network cracking still have many unresolved technical shortcomings: Traditional milling and repaving processes require large-area milling of the damaged area and repaving of hot-mix asphalt mixture. Construction relies on specialized equipment such as large pavers and rollers, resulting in high manpower and material costs, high repair costs per square meter, long construction cycles, and the need for prolonged traffic closures, which greatly impacts traffic flow. It is not suitable for scenarios such as urban arterial roads and main traffic arteries where long-term traffic closures are not permitted.
[0006] Conventional crack filling repair techniques often use flexible materials such as hot crack filling adhesive, ordinary cold-applied crack filling asphalt, and asphalt sealant. These materials can only fill single cracks with a relatively large width and cannot cover dense, fine cracks in a network cracked area. The materials cannot penetrate deep into the cracks and can only achieve surface sealing. They cannot form an integral bond with the original asphalt pavement. Under traffic loads and temperature shrinkage, problems such as material detachment and secondary cracking are very likely to occur, resulting in extremely poor repair durability.
[0007] Ordinary cold patch asphalt materials have core defects such as slow forming speed and low early strength. They require a long period of maintenance before traffic can be opened after construction. In addition, the material has insufficient compatibility with the original aged asphalt, poor resistance to water damage, and is prone to loosening and peeling. It cannot penetrate into the fine cracks and is difficult to cure the cracking disease. While existing cement-based repair materials have the advantages of rapid hardening and early strength, their elastic modulus differs greatly from that of asphalt pavement, resulting in poor interfacial compatibility and a tendency for cracking at the rigid-flexible interface. Furthermore, their poor fluidity prevents them from penetrating into the fine cracks of the network, allowing them to only achieve surface coverage and thus limiting their repair effectiveness.
[0008] Therefore, developing an asphalt network crack repair material that combines excellent permeability, resistance to shrinkage cracking, improved interfacial adhesion, resistance to water damage, strong overall bonding with the original asphalt pavement, fast molding, convenient construction, and low cost has become an urgent technical problem to be solved in this field. Summary of the Invention
[0009] In view of the shortcomings of the existing technology, the purpose of this invention is to provide an asphalt crack repair material and its preparation and construction methods, which can effectively penetrate into the fine cracks of asphalt pavement and form a continuous and integrated structure with the original pavement.
[0010] To achieve the above objectives, the present invention is implemented through the following technical solution: Firstly, an asphalt network crack repair material is composed of the following components in parts by weight: 35-40 parts magnesium phosphate cement, 3.5-4 parts sulfoaluminate cement, 5-10 parts mixing water, 22-26 parts quartz sand, and 25-30 parts emulsified asphalt.
[0011] Secondly, the preparation method of the above-mentioned asphalt network crack repair material includes the following steps: Weigh magnesium phosphate cement, sulfoaluminate cement and water, mix and stir to obtain cement-based composite admixture; Weigh out emulsified asphalt, add quartz sand and the cement-based composite admixture in sequence, and stir to obtain the asphalt network crack repair material.
[0012] Thirdly, the construction methods for the aforementioned asphalt network crack repair materials include: Clean the area to be repaired and dry it; The on-site mixed asphalt network crack repair material is spread to the area to be repaired according to the set thickness; Curing time: 1.5-2 hours.
[0013] The beneficial effects of this invention are as follows: This invention, through the composite modification of magnesium phosphate cement and sulfoaluminate cement, endows the repair material with excellent rapid-hardening and early-strength properties, accelerating the initial and final setting times and significantly shortening the time required for construction and maintenance. The repair material contains emulsified asphalt, exhibiting a stable and flowable state that effectively penetrates into the micro-cracks within the network of cracks. After curing, it forms a continuous and stable integrated structure with the original asphalt pavement, achieving a radical cure for network cracking, rather than merely surface sealing. Simultaneously, the material exhibits good compatibility with the original asphalt pavement, high elastic modulus matching, and high interfacial bond strength, avoiding problems such as interfacial cracking and detachment, effectively improving the integrity of the pavement structure and significantly extending the service life of the asphalt pavement. Detailed Implementation
[0014] It should be noted that the following detailed descriptions are exemplary and intended to provide further illustration of the invention. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0015] It should be noted that the terminology used herein is for the purpose of describing particular embodiments only and is not intended to limit the scope of exemplary embodiments according to the invention. As used herein, the singular form is intended to include the plural form as well, unless the context clearly indicates otherwise. Furthermore, it should be understood that when the terms "comprising" and / or "including" are used in this specification, they indicate the presence of features, steps, operations, devices, components, and / or combinations thereof.
[0016] One or more embodiments of the present invention provide an asphalt network crack repair material, which is composed of the following components in parts by weight: 35-40 parts magnesium phosphate cement, 3.5-4 parts sulfoaluminate cement, 5-10 parts mixing water, 22-26 parts quartz sand and 25-30 parts emulsified asphalt.
[0017] Among the above components, the composite modification of magnesium phosphate cement and sulfoaluminate cement endows the repair material with excellent rapid hardening and early strength characteristics, while realizing volume compensation during the curing process and avoiding shrinkage cracking. By adjusting the material ratio, the repair material is made into a stable flowable state with an initial flowability ≥180mm. Emulsified asphalt enables the repair material to form a continuous and stable integral structure with the original asphalt pavement after curing, thus achieving a radical cure for network cracking. Quartz sand is used to support the repair material inside the network cracks, reducing the shrinkage of the repair material and improving its support capacity, preventing the repair material from further developing network cracking.
[0018] Optionally, the quartz sand has a particle size of 0.5~1mm, which can effectively penetrate into the interior of fine cracks with a width of ≥0.2mm.
[0019] Optionally, the quartz sand is continuously graded with a mud content of ≤0.5% and a crushing value of ≤15%. This gradation and performance parameter setting allows the quartz sand to form a uniform and dense rigid skeleton support system inside the repair material. The absence of mud impurities can completely avoid the problems of skeleton interface bonding failure and material loosening and falling off. The extremely low crushing value can ensure the long-term load-bearing stability of the skeleton, effectively resist the squeezing of traffic loads and temperature deformation stress, minimize the risk of curing shrinkage and deformation cracking of the repair material, and significantly improve the overall strength and durability of the repair layer.
[0020] Optionally, the emulsified asphalt is cationic emulsified asphalt with a solid content of 55-65%; its storage stability meets the relevant requirements of the "Technical Specification for Construction of Highway Asphalt Pavement" JTG F40, ensuring excellent compatibility with the original asphalt pavement; cationic emulsified asphalt has significant performance advantages over anionic and nonionic emulsified asphalt. Asphalt pavement aggregates and aged asphalt surfaces are mostly weakly acidic, cationic emulsified asphalt can form a strong physical adsorption bond with the original pavement asphalt and aggregates through charge adsorption, with a bonding strength far higher than other types of emulsified asphalt; at the same time, its demulsification and curing speed is moderate, its film density is better, and its resistance to water penetration and aging is stronger, which can effectively improve the integrity of the repair material and the original pavement, avoid interface water seepage, delamination, and peeling problems, and greatly improve the durability of the repair structure.
[0021] Optionally, the sulfoaluminate cement is rapid-hardening sulfoaluminate cement; preferably, it is grade 42.5 rapid-hardening sulfoaluminate cement; the magnesium phosphate cement is rapid-hardening magnesium phosphate cement; the principle of their compounding is as follows: rapid-hardening magnesium phosphate cement has an extremely fast hydration rate, providing an ultra-early strength effect, enabling rapid curing and shaping of the material, and short-term opening to traffic, thus compensating for the insufficient early strength of ordinary cement; the hydration products of rapid-hardening sulfoaluminate cement can fill the micropores formed by the hydration of magnesium phosphate cement, achieving micro-expansion compensation and offsetting the curing shrinkage defects of magnesium phosphate cement. The two work together to achieve the effect of "rapid hardening and early strength + shrinkage-free dense curing". This invention does not use ordinary silicate cement, slag cement, or other cements for compounding because: ordinary silicate cement has slow hydration, poor early strength, and large shrinkage, which cannot meet the requirements for rapid traffic opening, and uneven hydration heat release can easily cause cracking of the repair layer; slag cement and fly ash cement have extremely low early strength, long molding cycle, and poor impermeability and adhesion, making them unsuitable for rapid repair of asphalt pavement. When the content of magnesium phosphate cement is too high, the hydration reaction of the material is too fast, the workable time after mixing is greatly shortened, and problems such as premature clumping and inability to be spread and constructed are likely to occur. In addition, the curing brittleness increases and the toughness is insufficient, making it easy to crack under the impact of traffic loads in the later stage. When the content of magnesium phosphate cement is too low, the early strength performance of the material is greatly reduced, and the core effect of rapid traffic opening in 1.5 hours cannot be achieved. The curing speed is slow, the curing cycle is prolonged, and the technical advantage of rapid repair is lost.
[0022] One or more embodiments of the present invention provide a method for preparing the above-mentioned asphalt network crack repair material, comprising the following steps: Weigh magnesium phosphate cement, sulfoaluminate cement and water, mix and stir to obtain cement-based composite admixture; Weigh out emulsified asphalt, add quartz sand and the cement-based composite admixture in sequence, and stir to obtain the asphalt network crack repair material.
[0023] The above method employs a two-step, multi-stage mixing process, rather than mixing all materials at once. The core advantages and principles are as follows: First, it avoids the hydration disorder problems that occur when materials are mixed all at once. Cement-based powder hydrates rapidly upon contact with water; if directly mixed with emulsified asphalt and quartz sand, it leads to insufficient cement hydration, localized clumping and agglomeration, and also damages the colloidal stability of the emulsified asphalt, causing asphalt demulsification, stratification, and material failure. Second, mixing the cement-based admixture separately first ensures that both types of cement and water are fully and uniformly hydrated, forming a stable cementitious substrate, providing a uniform and early-strength foundation for subsequent materials. Third, multi-stage mixing achieves a layered and uniform composite of the rigid skeleton, cementitious substrate, and flexible asphalt substrate, avoiding the problems of quartz sand clumping and uneven asphalt distribution. The final product has better fluidity, uniformity, and stability, with more balanced penetration and curing strength, completely solving the problems of material stratification, clumping, uneven performance, and inconsistent repair effects caused by one-step mixing.
[0024] Optionally, the mixing method includes stirring at a speed of 50~70 r / min for 2~4 min.
[0025] Optionally, the stirring method includes: continuously stirring at a speed of 70~90 r / min for 4~6 min.
[0026] Optionally, the ambient temperature must be controlled during the mixing and storage of emulsified asphalt. The suitable temperature range for construction is 5℃~35℃. Mixing and construction are strictly prohibited in environments with temperatures below 5℃ or above 35℃. Low temperatures will cause the colloidal stability of emulsified asphalt to decrease, the demulsification speed to be too slow, the material fluidity to decrease, and it will be unable to effectively penetrate cracks. High temperatures will accelerate the premature demulsification of emulsified asphalt and the rapid hydration of cement, causing the material to quickly clump together and fail, greatly shortening the construction time and making normal paving operations impossible. Strict temperature control can ensure the stability of material mixing and the feasibility of construction.
[0027] One or more embodiments of the present invention provide a construction method for the above-mentioned asphalt network crack repair material, comprising: Clean the area to be repaired and dry it; The on-site mixed asphalt crack repair material is spread to the area to be repaired according to the set thickness. After spreading, the surface of the repair material is flush with the surrounding original asphalt pavement and will not be higher than the surrounding pavement. No further grinding or leveling is required, ensuring the smoothness of the road surface and driving comfort. To enhance the effect of the material penetrating the cracks, a lightweight leveling scraper can be used for low-speed repeated scraping and slight vibration after spreading. The micro-pressure action will push the fluid repair material to fully penetrate into the depths of the fine cracks of 0.2mm and above, completely filling the crack cavities and eliminating the problems of gaps and voids. This ensures that the repair material is fully integrated and bonded to the original pavement structure to form an integral structure.
[0028] Curing time: 1.5-2 hours.
[0029] During the above process, the on-site mixing requirements are as follows: all raw materials must be accurately weighed and added according to the proportions, and it is strictly forbidden to arbitrarily increase or decrease the amount of components; the mixing equipment must be clean and dry, free from standing water, residual hardened materials, and impurities; the mixing speed and duration of the two steps must be strictly implemented according to the process parameters to ensure that the materials are uniform, without lumps, stratification, or dry powder. Mixing and construction time window: Under standard temperature (20~25℃) conditions, the operable construction time after the materials are mixed is 30~40 minutes. All paving and leveling work must be completed within this time. It is strictly forbidden to use materials that have been left to stand for too long or show signs of initial setting to avoid material failure and substandard repair quality.
[0030] Optionally, the thickness of the asphalt network crack repair material can be determined based on the depth of the network crack in the area to be repaired. When the network crack in the area to be repaired is a shallow, dense, and fine network crack with a crack depth of 3 to 5 mm, and the area of dense network cracks accounts for 60% to 90% of the total area of the area to be repaired, and there are no large-area potholes or deep through cracks, the paving thickness is 2 to 2.5 mm.
[0031] Optionally, the curing temperature is 5~35℃, and after curing and molding, the compressive strength is ≥3.5MPa. Once the design requirements for opening to traffic are met, the enclosure can be removed and traffic can be opened.
[0032] The present invention will be further described below with reference to specific embodiments.
[0033] Example 1 This embodiment provides a novel asphalt network crack repair material, which, based on 100% of the total material mass, has the following precise proportions: 37% magnesium phosphate cement, 3.7% grade 42.5 rapid-hardening sulfoaluminate cement, 7.4% mixing water, 24.1% 0.5~1mm clean quartz sand, and 27.8% 60% solids content cationic emulsified asphalt.
[0034] Among them, the 3-hour compressive strength of magnesium phosphate cement is 22 MPa; the quartz sand has a mud content of 0.3% and a crushing value of 12%; and the storage stability of emulsified asphalt meets the requirements of JTG F40 specification.
[0035] The preparation method of the novel asphalt network crack repair material in this embodiment includes the following specific steps: Step S1: Preparation of cement-based composite admixture: Accurately weigh magnesium phosphate cement, sulfoaluminate cement and mixing water according to the above proportions, put the three into a vertical mortar mixer at the same time, and stir at a speed of 60 r / min for 3 minutes until the material is uniform, without lumps or dry powder agglomeration, to obtain cement-based composite admixture. Step S2: Substrate mixing: Weigh 60% solids content cationic emulsified asphalt according to the above ratio and place it in a low-speed mixing tank. First, add the weighed 0.5~1mm quartz sand and stir at 80r / min for 2min to make the quartz sand evenly dispersed in the emulsified asphalt. Then add the cement-based composite admixture prepared in step S1 and continue stirring. Step S3: Finished product mixing: Maintain a stirring speed of 80 r / min for 5 minutes until the mixture is in a uniform, stable, and flowable fluid state, without stratification, sedimentation, or clumping, thus obtaining the new asphalt network crack repair material.
[0036] The specific steps of the construction method for the novel asphalt network crack repair material in this embodiment are as follows: Step T1: Road surface pretreatment: For the asphalt pavement cracked area to be repaired, first use a wire brush to remove loose asphalt aggregate and debris from the surface, then use a powerful blower to remove dust and debris from the cracks, and at the same time remove the accumulated water in the area. The moisture content of the area to be repaired is 3.2%, which meets the construction requirements. In this embodiment, the area to be repaired is a shallow dense cracked area with a crack depth of 3~5mm and a dense cracked area accounting for 75%, which is suitable for a standard paving thickness of 2mm.
[0037] Step T2: Material Spreading: The newly mixed asphalt network crack repair material is evenly poured onto the network crack area to be repaired, and spread evenly using an asphalt paving rake or a special leveling tool. Since this embodiment is suitable for shallow severe network cracking conditions, the crack depth in the area to be repaired is 3-5mm, and the network crack coverage is about 75%, which is the most common early-stage dense network cracking condition on roads. A 2mm spreading thickness can completely cover the surface crack area, while reserving space for material penetration, which is suitable for the filling and repair needs of shallow cracks. The spreading thickness is strictly controlled at 2mm. During the spreading process, the auxiliary operation of low-speed reciprocating light pressure and uniform leveling with a leveling tool is used to ensure that the material completely covers the network crack area and fully penetrates into the crack. After spreading, the road surface is smooth and flat, without any missed areas, accumulation, or obvious scratches. All spreading operations are completed within 30 minutes after the material is mixed, which meets the construction time window requirements.
[0038] Step T3: Curing and Opening to Traffic: The paved construction area is fully enclosed for curing using warning cones and tape. The ambient temperature is 25℃ and the curing time is 1.5 hours. After on-site rebound testing, the material compressive strength reaches 3.8MPa, which meets the strength requirements for opening to traffic. The warning facilities are then removed and traffic is opened.
[0039] Performance testing The novel asphalt network crack repair material prepared in this embodiment was subjected to performance testing in accordance with the relevant standards of "Test Procedures for Asphalt and Asphalt Mixtures in Highway Engineering" JTG E20 and "Technical Specifications for Construction of Highway Pavement Base Course" JTG / T F20. The test results are shown in Table 1.
[0040] Table 1
[0041] Test results show that the novel asphalt network crack repair material meets all design requirements and relevant road maintenance standards, possessing excellent fluidity, permeability, rapid hardening and early strength characteristics, and interfacial bonding performance, fully satisfying the repair needs of asphalt pavement network cracking. The volume compensation performance of this invention can be directly verified by the 28-day drying shrinkage rate: magnesium phosphate cement exhibits a certain shrinkage trend during hydration, while sulfoaluminate cement hydrates to produce expansive products such as ettringite. The combination of these two components can achieve micro-expansion compensation throughout the curing process, offsetting system shrinkage. Test results show that the 28-day drying shrinkage rate of the material in this embodiment is only 2.1 × 10⁻⁶. -4 The shrinkage rate is far lower than that of conventional cement-based repair materials, proving that the dual-cement composite system effectively offsets curing shrinkage, avoids secondary cracking of the repair layer due to drying shrinkage, and verifies the technical effect of the volume compensation design.
[0042] Example 2 A type of asphalt network crack repair material is composed of the following components in parts by weight: 35 parts magnesium phosphate cement, 3.5 parts grade 42.5 rapid-hardening sulfoaluminate cement, 5 parts mixing water, 22 parts clean quartz sand with a particle size of 0.5~1mm, and 25 parts cationic emulsified asphalt with 60% solids content. The performance requirements of each raw material, preparation process steps, and parameters are exactly the same as in Example 1.
[0043] The performance was tested according to the method in Example 1, and the results are shown in Table 2.
[0044] Table 2
[0045] The results show that this embodiment is a low-value scheme of component ratio, and all performance indicators meet the design and specification requirements. It can achieve effective network crack repair and rapid traffic opening in 1.5 hours, proving that the ratio of the present invention also has stable technical effects in the low value range.
[0046] Example 3 A type of asphalt network crack repair material is composed of the following components in parts by weight: 40 parts magnesium phosphate cement, 4 parts grade 42.5 rapid hardening sulfoaluminate cement, 10 parts mixing water, 26 parts clean quartz sand with a particle size of 0.5~1mm, and 30 parts cationic emulsified asphalt with 60% solid content.
[0047] The performance requirements of each raw material, preparation process steps and parameters are exactly the same as those in Example 1.
[0048] The performance was tested according to the method in Example 1, and the results are shown in Table 3.
[0049] Table 3
[0050] The results show that this embodiment is a high-value scheme of component ratio, and all performance indicators are better than the technical requirements. The early strength and anti-shrinkage performance are more outstanding, proving that the ratio of the present invention is also stable and effective in the high value range, and the overall ratio range has good universality and reliability.
[0051] Comparative Example 1 A type of asphalt network crack repair material is composed of the following components in parts by weight: 37 parts magnesium phosphate cement, 2.0 parts grade 42.5 rapid hardening sulfoaluminate cement, 7.4 parts mixing water, 24.1 parts clean quartz sand with a particle size of 0.5~1mm, and 27.8 parts cationic emulsified asphalt with 60% solid content.
[0052] The difference from Example 1 is that the amount of sulfoaluminate cement is reduced. All other raw material requirements and preparation methods are exactly the same as in Example 1.
[0053] The performance was tested according to the method in Example 1, and the results are shown in Table 4.
[0054] Table 4
[0055] Results indicate that this comparative example could not yield a product that fully meets the performance requirements; the core defects are volume compensation failure and insufficient early strength performance. Disadvantages of insufficient sulfoaluminate cement: 1. The volume compensation effect is greatly weakened, the curing shrinkage of the system is significantly increased, the 28-day drying shrinkage rate exceeds the standard, the repair layer is prone to dry shrinkage microcracks, the water damage resistance is reduced, the freeze-thaw splitting strength ratio does not meet the standard, and the long-term durability is insufficient. 2. Early strength performance degradation: the compressive and flexural strengths after 1.5 hours cannot meet the requirements for opening to traffic, thus failing to achieve the core function of rapid traffic opening; 3. The density of hydration products decreases, the overall strength and impermeability of the repair layer decrease, rainwater can easily seep into the interface causing delamination, and the service life of the repair is shortened.
[0056] Comparative Example 2 A type of asphalt network crack repair material is composed of the following components in parts by weight: 37 parts magnesium phosphate cement, 6 parts grade 42.5 rapid hardening sulfoaluminate cement, 7.4 parts mixing water, 24.1 parts clean quartz sand with a particle size of 0.5~1mm, and 27.8 parts cationic emulsified asphalt with 60% solid content.
[0057] The difference from Example 1 is that the amount of sulfoaluminate cement is increased.
[0058] The requirements for all other raw materials and the preparation methods are exactly the same as in Example 1.
[0059] The performance was tested according to the method in Example 1, and the results are shown in Table 5.
[0060] Table 5
[0061] Results indicate that this comparative example could not yield a product that fully meets the performance requirements. The core defects are increased material brittleness and failure of workability and interfacial bonding performance. Disadvantages of excessive sulfoaluminate cement: 1. The hydration reaction is too fast, the initial setting time is greatly shortened, the on-site construction time window is less than 20 minutes, the material is prone to clumping in advance, and it cannot be properly spread and penetrated, which significantly increases the difficulty of construction. 2. The material is too rigid and not tough enough, and its flexural strength does not meet the standard. It is prone to brittleness under the impact of traffic load and temperature deformation, and the repair layer is prone to cracking and flaking. 3. If the proportion of cement-based components is too high, the compatibility with emulsified asphalt will decrease, the interfacial bond strength will be reduced, the asphalt phase and cement phase will easily separate, the bond between the repair layer and the original pavement will be insufficient, delamination and peeling will be easy, and the water damage resistance will be reduced.
[0062] Comparative Example 3 A type of asphalt network crack repair material is composed of the following components in parts by weight: 37 parts magnesium phosphate cement, 3.7 parts grade 42.5 rapid hardening sulfoaluminate cement, 7.4 parts mixing water, 24.1 parts clean quartz sand with a particle size of 0.5~1mm, and 20 parts cationic emulsified asphalt with 60% solid content.
[0063] The difference from Example 1 is that the amount of emulsified asphalt is reduced. All other raw material requirements and preparation methods are exactly the same as in Example 1.
[0064] The performance was tested according to the method in Example 1, and the results are shown in Table 6.
[0065] Table 6
[0066] Results show that this comparative example failed to produce a product meeting performance requirements; the core defects were in penetration performance, adhesion performance, and toughness failure. Disadvantages of insufficient emulsified asphalt: 1. The material's fluidity has decreased significantly, and the minimum penetration crack width exceeds the standard. It cannot penetrate into the fine network cracks at the 0.2mm level, and can only achieve surface coverage, but cannot cure the network crack disease. 2. The compatibility and adhesion with the original asphalt pavement are significantly reduced, the interfacial bond strength is substandard, the repair layer is prone to delamination and peeling from the original pavement, and rainwater can easily seep in and cause secondary damage. 3. The material has insufficient flexibility, increased brittleness, low flexural strength, poor resistance to temperature deformation and load impact, and is prone to cracking, loosening and falling off, resulting in poor repair durability.
[0067] Comparative Example 4 A type of asphalt network crack repair material is composed of the following components in parts by weight: 37 parts magnesium phosphate cement, 3.7 parts grade 42.5 rapid hardening sulfoaluminate cement, 7.4 parts mixing water, 24.1 parts clean quartz sand with a particle size of 0.5~1mm, and 33 parts cationic emulsified asphalt with a solid content of 60%.
[0068] The difference from Example 1 is that the amount of emulsified asphalt is increased. All other raw material requirements and preparation methods are exactly the same as in Example 1.
[0069] The performance was tested according to the method in Example 1, and the results are shown in Table 7.
[0070] Table 7
[0071] Results show that this comparative example could not produce a product that met the performance requirements. The core defects were insufficient early strength and overall strength, making it impossible to quickly open the road to traffic. Disadvantages of excessive emulsified asphalt: 1. The proportion of cementitious materials is diluted, the rapid hardening and early strength performance is significantly reduced, the initial setting time is prolonged, and the 1.5-hour compressive strength cannot meet the requirements for opening to traffic, thus failing to achieve the core function of rapid traffic opening. 2. The material has insufficient overall stiffness, fails to meet the 28-day long-term strength standard, has poor high-temperature stability, and the repair layer is prone to softening and deformation under high-temperature conditions in summer. It also has weak resistance to rutting and insufficient long-term load-bearing capacity. 3. The material cures and forms slowly, extending the curing cycle and increasing the duration of traffic closure. Additionally, the surface tends to stick to wheels after forming, making it easy for vehicles to lift and detach it in the initial stages of reopening to traffic.
[0072] In summary, the single-variable verification through four sets of comparative examples shows that the component ratio range defined by this invention is the optimal range for achieving comprehensive performance of "rapid hardening and early strength, excellent permeability, high bonding strength, low shrinkage and crack resistance, and durable stability". Any component deviating from the ratio range of this invention will cause the core performance indicators to fail, making it impossible to simultaneously meet the requirements of rapid traffic opening, deep repair, and long-term durability network crack repair. This fully demonstrates the creativity and technical rationality of the ratio design of this invention.
[0073] The asphalt crack repair material provided by the technical solution of this invention has a wide range of applications and strong versatility. The repair material of this invention can specifically repair various early-stage defects in asphalt pavements, such as alligator cracking, network cracking, and asphalt surface peeling. It can be used for repairing small-area local defects as well as for overall repair of large-area network cracked areas. It is suitable for maintenance and repair of various asphalt pavements such as high-grade highways, urban roads, park roads, and parking lots. It can be applied normally within an ambient temperature range of 5℃ to 35℃. The construction process is simple, requiring no large equipment or professional personnel. It can be prepared on-site, and the mixing process is simple and controllable. Construction only requires simple paving and leveling tools, without the need for large pavers, road rollers or other professional equipment, and no special operation personnel. 2-3 people can complete the entire construction process, which greatly reduces the construction threshold and manpower input. Raw materials are readily available and repair costs are low. All raw materials used are conventional building materials for road engineering, making procurement convenient and costs controllable. According to actual calculations, the cost of repair materials per square meter of asphalt cracked pavement is only 25 yuan, which is far lower than traditional repair processes such as milling and repaving, micro-surfacing, and ultra-thin wearing layers, significantly reducing the economic investment in road maintenance.
[0074] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Various modifications and variations can be made to this application by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the protection scope of this application.
Claims
1. A material for repairing asphalt network cracks, characterized in that, It is composed of the following components in parts by weight: 35-40 parts magnesium phosphate cement, 3.5-4 parts sulfoaluminate cement, 5-10 parts mixing water, 22-26 parts quartz sand, and 25-30 parts emulsified asphalt.
2. The asphalt network crack repair material according to claim 1, characterized in that, The particle size of the quartz sand is 0.5~1mm.
3. The asphalt network crack repair material according to claim 1, characterized in that, The quartz sand is continuously graded, with a mud content of ≤0.5% and a crushing value of ≤15%.
4. The asphalt network crack repair material according to claim 1, characterized in that, The emulsified asphalt is a cationic emulsified asphalt with a solid content of 55-65%.
5. The asphalt network crack repair material according to claim 1, characterized in that, The sulfoaluminate cement is a rapid-hardening sulfoaluminate cement; preferably, it is grade 42.5 rapid-hardening sulfoaluminate cement; the magnesium phosphate cement is a rapid-hardening magnesium phosphate cement.
6. A method for preparing an asphalt network crack repair material as described in any one of claims 1-5, characterized in that, Including the following steps: Weigh magnesium phosphate cement, sulfoaluminate cement and water, mix and stir to obtain cement-based composite admixture; Weigh out emulsified asphalt, add quartz sand and the cement-based composite admixture in sequence, and stir to obtain the asphalt network crack repair material.
7. The method for preparing the asphalt network crack repair material according to claim 6, characterized in that, The mixing method includes stirring at a speed of 50~70 r / min for 2~4 min; Alternatively, the stirring method may include: continuously stirring at a speed of 70-90 r / min for 4-6 min.
8. The method for preparing the asphalt network crack repair material according to claim 6, characterized in that, The mixing and storage temperature of emulsified asphalt is 5℃~35℃.
9. A construction method based on the asphalt network crack repair material as described in any one of claims 1-5, characterized in that, Clean the area to be repaired and dry it; The on-site mixed asphalt network crack repair material is spread to the area to be repaired according to the set thickness; Curing time: 1.5-2 hours.
10. The construction method as described in claim 9, characterized in that, The thickness of the asphalt network crack repair material is determined based on the depth of the network crack in the area to be repaired. When the network crack in the area to be repaired is a shallow, dense, and fine network crack with a crack depth of 3-5 mm, and the area of dense network cracks accounts for 60%-90% of the total area to be repaired, the paving thickness is 2-2.5 mm.